1. Nov 16, 2009

### 1/2"

Hey there!
I just want to know that this problem
(t-2)^2=36
can be solved by squaring t-2 so we have the answer as t=8 ,-4
but suppose if I rather do like this that I square root 36 and remove the power on t-2
then

or t- 2= 6
or t=8
here also i get the 8 result but i dont get the -4 one.
But I think it isnt a wrong way to deal ,is it?:uhh:
I would be very much happy for any help!!

2. Nov 16, 2009

### rzaidan

Hi 1/2"
When you take the square root for both sides ,you are to take the absolute values when removing squares; that is t-2=6 or t-2=-6 so you will have
t=8 , t=-4 as you get.
Best regards

3. Nov 16, 2009

### Staff: Mentor

Here's another way to look at this without absolute values.
(t - 2)2 = 36
<==> (t - 2)2 - 36 = 0
<==> ((t - 2) - 6)((t - 2) + 6) = 0
<==> (t - 8)(t + 4) = 0
<==> t = 8 or t = -4

4. Nov 16, 2009

### 1/2"

Thanks a lot for helping !!

5. Nov 17, 2009

### rzaidan

Hi Mark44 ,
The problem was in ((removing squares)) from both sides by taking square roots and not in finding another way to solve the problem. In general, thanks a lot for you...........
Best Regards